Decoding the regulatory networks of Proteus mirabilis under succinic acid stress: a multi-omics approach - Yang, Aoyu; Cai, Yuqing; Zhang, Ziyi; Xu, Yafang; Shen, Chen; Wang, Wei; You, Haiqing; Sha, Shanshan; Li, Huajun; Li, Xiancheng (Frontiers in Cellular and Infection Microbiology, 2025)
Proteus mirabilis, a major catheter-associated urinary tract infection pathogen, forms antibiotic-resistant crystalline biofilms. Our study demonstrates succinic acid’s multimodal inhibition of P.mirabilis via multi-omics analyses. At 15 mM, succinic acid reduced bacterial growth (≥70%) and biofilm formation (≥50%). Metabolomics revealed that succinic acid treatment induces dysregulation in the tryptophan and arginine metabolism, nucleotide biosynthesis, and tricarboxylic acid cycle in P.mirabilis. Transcriptomics revealed downregulated ribosomal genes, oxidative phosphorylation, and efflux pumps, alongside upregulated arginine transport. Proteomics showed suppression of T6SS virulence factors and iron acquisition proteins. We propose that succinic acid reduces K6 acetylation of the histone-like nucleoid structuring protein, enhancing its oligomerization to repress T6SS genes and inhibit biofilm formation. By targeting metabolism, virulence, and stress adaptation, succinic acid circumvents single-target resistance, offering a strategy to combat multidrug-resistant P.mirabilis through biofilm disruption and pathogenicity suppression.